2018
DOI: 10.1186/s13018-018-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of locking compression plate via posterolateral approach in the treatment of distal femoral fractures: a new approach

Abstract: BackgroundDistal femur fractures are difficult to manage, and the selection of implant approach for internal fixation remains controversial. This study explores the clinical outcome of treating distal femoral fractures with a locking compression plate using a posteriolateral novel approach.MethodsTwenty patients with distal femoral fractures were included in our study, and all patients underwent fixation of the fracture using a locking compression plate through a posterolateral approach. The postoperative frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, the lateral approach may result in insufficient posterior exposure, making fixation based on the AO principle difficult. Another study reported that lateral plate fixation was performed using a posterolateral approach [9] , and intra-articular exposure was considered difficult. Another study reported that osteotomy of Gerdy's tubercle is useful for the extensive expansion of Hoffa fragments and reduction of the articular surface [10] , the risk of osteotomy fragment nonunion remains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lateral approach may result in insufficient posterior exposure, making fixation based on the AO principle difficult. Another study reported that lateral plate fixation was performed using a posterolateral approach [9] , and intra-articular exposure was considered difficult. Another study reported that osteotomy of Gerdy's tubercle is useful for the extensive expansion of Hoffa fragments and reduction of the articular surface [10] , the risk of osteotomy fragment nonunion remains.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 16 postpolio patients, a locked compression plate was applied to distal femur fractures [10] . Locked compression plates are one of the gold standard treatment modalities in distal femoral fractures [11] . However, anatomic locking plates or intramedullary nailing may not be appropriate for postpolio fractures, so custom-made implants or implants for different anatomic regions are recommended for postpolio femoral fractures [12] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, positioning of the patient over a fracture table for nailing and applying traction is difficult because of flexion deformity at knee [ 16 ]. Locked compression plates are one of the gold standard treatment options in distal femur fractures [ 17 ] which was also proved to be true in poliotic distal femur fractures [ 7 ]. Since poor blood supply and bone healing capacity were anticipated, absolute stability rather than relative was given preference.…”
Section: Discussionmentioning
confidence: 99%